The great pretenders? Individuals’ responses to threats to their remote worker identities - Felix, Bruno; Tiussi, Bruno Lorencini; Mahadevan, Jasmin; Dias, Rogério Correia (Frontiers in Psychology, 2023)
This study aims to understand a) how remote workers respond to threats to their identity and b) the conditions in which each coping response tends to occur more frequently. To this end, we pursued a grounded theory approach, conducting interviews with 71 individuals who chose to work remotely. Our model and theoretical propositions create insights into how remote workers respond to negative stigma from a range of origins. While some responses lead to restructuring the remote workers' identity (identity restructuring responses), others involve keeping the enactment of such identity (identity-preserving responses) or maintaining a paradoxical relationship between restructuring and preserving the identity (paradoxical identity work responses). We also theorise on the conditions under which each response is more likely to occur.